Most na Soči Arheološke raziskave v letih 2000-2016 na levem bregu Idrijce = The 2000-2016 archaeological investigations on the left bank of the Idrijca - Milnar, Miha (Opera Instituti Archaeologici Sloveniae, 2020)
Most na Soči is an archaeological site of key importance in the Posočje region and also one that witnessed most extensive investigations. Remains of its rich distant past have been coming to light over the last century and a half, either as chance finds or through archaeological excavations of the settlement from the Bronze, Iron and Roman Ages, as well as the associated cemeteries.This book presents the recent investigations on the left bank of the Idrijca, where a vast Iron Age cemetery has been known since the end of the 19th century. At its northern edge, a total of 88 graves were excavated by the Tolminski muzej in 2000-2016, when three locations were investigated: Pucarjev rob, Repelc and Lipičarjev vrt. Most of the graves date to the Iron Age, a dozen to the Roman period and one to the Early Middle Ages. In their immediate vicinity, a contemporary cremation pit and a stone drywall were discovered, under the graves also habitation remains from the Late Bronze Age.